ANALYSIS OF PROFIT-SHARING-BASED FINANCING INSTRUMENTS UTILIZATION FOR SUSTAINABLE GROWTH IN ISLAMIC MICROFINANCE INSTITUTIONS: EMPIRICAL EVIDENCE FROM KSPPS BMT UGT NUSANTARA - Abdussalam, Abdussalam; Asnawi, Nur; Yuliana, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the utilization of profit-sharing-based financing instruments on the sustainable growth of KSPPS BMT UGT Nusantara. Employing a qualitative method with case study approach and literature review analysis, this research involves key informants from BMT UGT Nusantara's organizational structure. The findings demonstrate that profit-sharing-based financing has a significant impact on the sustainable growth of KSPPS BMT UGT Nusantara, as evidenced by the growth in assets, third-party funds, and capital structure. However, it also faces challenges including default risk, accounting system weaknesses, and limited member understanding of profit-sharing-based Mudharabah and Musyarakah contracts. This study reveals the importance of enhancing risk management systems, member education through Islamic financial literacy, and product innovation to optimize the positive impact of profit-sharing-based financing instruments on BMT UGT's sustainable growth. This research contributes to Islamic economics literature by highlighting the specific dynamics of profit-sharing-based financing within the context of BMT in Indonesia.